Diagnostic yield and accuracy in a tertiary referral syncope unit validating the ESC guideline on syncope: a prospective cohort study. Issue 5 (21st November 2020) - de Jong, Jelle S Y; Blok, Minou R Snijders; Thijs, Roland D; Harms, Mark P M; Hemels, Martin E W; de Groot, Joris R; van Dijk, Nynke; de Lange, Frederik J
Abstract: Aims : To assess in patients with transient loss of consciousness the diagnostic yield, accuracy, and safety of the structured approach as described in the ESC guidelines in a tertiary referral syncope unit. Methods and results : Prospective cohort study including 264 consecutive patients (≥18 years) referred with at least one self-reported episode of transient loss of consciousness and presenting to the syncope unit between October 2012 and February 2015. The study consisted of three phases: history taking (Phase 1), autonomic function tests (AFTs) (Phase 2), and after 1.5-year follow-up with assessment by a multidisciplinary committee (Phase 3). Diagnostic yield was assessed after Phases 1 and 2. Empirical diagnostic accuracy was measured for diagnoses according to the ESC guidelines after Phase 3. The diagnostic yield after Phase 1 (history taking) was 94.7% (95% CI: 91.1–97.0%, 250/264 patients) and increased to 97.0% (93.9–98.6%, 256/264 patients) after Phase 2. The overall diagnostic accuracy (as established in Phase 3) of the Phases 1 and 2 diagnoses was 90.6% (95% CI: 86.2–93.8%, 232/256 patients). No life-threatening conditions were missed. Three patients died, two unrelated to the cause of transient loss of consciousness, and one whom remained undiagnosed. Conclusion : A clinical work-up at a tertiary syncope unit using the ESC guidelines has a high diagnostic yield, accuracy, and safety. History taking (Phase 1) is the most important diagnostic tool. Autonomic function tests never changed the Phase 1 diagnosis but helped to increase the certainty of the Phase 1 diagnosis in many patients and yield additional diagnoses in patients who remained undiagnosed after Phase 1. Diagnoses were inaccurate in 9.4%, but no serious conditions were missed. This is adequate for clinical practice.